Conforming a Voluntary Medical Leave of Absence Policy to Recent Interpretations of Disability Law. Issue 1 (2nd January 2016) - Meilman, Philip W.
ABSTRACT: In 2011, Georgetown University worked to revise its medical leave of absence (MLOA) policy to be in conformity with evolving standards and interpretations of disability law as it pertains to university students. The article describes the new policy, which was reviewed and approved by the U.S. Department of Education's Office for Civil Rights. Implications are discussed for both Georgetown University and other institutions.